2020
DOI: 10.25122/jml-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Children Food and Nutrition Literacy - a New Challenge in Daily Health and Life, the New Solution: Using Intervention Mapping Model Through a Mixed Methods Protocol

Abstract: Food and nutrition literacy is a fundamental and new idiom among health policymakers. Improving children’s food and nutrition literacy is a fundamental task, and it requires detailed planning. The aim of this study is to design, implement, and evaluate a food and nutrition literacy promotion intervention in elementary school children based on the Intervention Mapping model. This is a sequential study to design, implement, and evaluate a food and nutrition literacy promotion intervention in elementary school ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
(33 reference statements)
0
3
0
1
Order By: Relevance
“…Other studies that used IM to design and implement nutrition interventions have reported positive effects on improving short-term outcomes ( 22 , 31 ). Based on such evidence, the present study applied the steps of the intervention mapping approach to design, implement and evaluate the intervention ( 17 , 22 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that used IM to design and implement nutrition interventions have reported positive effects on improving short-term outcomes ( 22 , 31 ). Based on such evidence, the present study applied the steps of the intervention mapping approach to design, implement and evaluate the intervention ( 17 , 22 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention mapping (IM) is a process and unique approach for developing theory and evidence-based health education programs. Different studies have been performed to solve health problems using an interventional mapping approach, including a self-care training program for type 2 diabetic patients ( 31 ), designing educational interventions to promote food and nutrition literacy in primary school children ( 32 ), designing, implementing, and evaluation of community-based and school-based multifaceted intervention to sustainably increase fruit and vegetable consumption among children ( 33 ). The implementation of IM as a roadmap for designing and planning programs to address health problems has attracted the attention of researchers and planners in recent years ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intervention-mapping model, which uses both quantitative and qualitative methods, allows for a comprehensive understanding of the interconnections and complexities of social norms, human behavior, and social determinants of health. Incorporating multiple research approaches may provide a more nuanced and holistic perspective [22]. In conclusion, interventions for children's food literacy have a positive impact, and it is important to engage children in practical food-related experiences.…”
Section: Do Research Projects Promote Food/nutrition Literacy?mentioning
confidence: 99%
“…Örneğin, Johanne ve ark.nın 2014 yılında yaptığı bir çalışmada, uzun süreli ketojenik diyet ile beslenmenin dislipidemi ve glukoz intoleransına neden olduğu belirlenmiştir (15). Gıda ve beslenme okuryazarlığının gelişimi, doğru besin seçimi ve doğru gıda örüntüsünün sağlanmasında önemli bir faktördür (16). Taylor ve ark.nın 2019 yılında yaptığı çalışmada, düşük düzeyde beslenme okuryazarlığına sahip bireylerin, batı tarzı diyet ile ilişkilendirilen gıdaları daha fazla tükettikleri (kızarmış besin, şeker içeren içecekler, kırmızı et ve işlenmiş gıda), iyi düzeyde beslenme okuryazarlığına sahip bireylerin ise Akdeniz diyetine özgü besinleri (sebzeler, zeytinyağı ve sert kabuklu yemişler) daha fazla tercih ettikleri bildirilmiştir (17).…”
Section: Introductionunclassified